Trade Policy to Catalyze Export Diversification : What Should Landlocked Fragile Countries Do? The Cases of Mali, Chad, and Niger - Lopez-Calix, Jose; Pitigala, Nihal (World Bank, Washington, DC, 2019)
The landlocked and fragile countries Mali, Niger, and Chad have suffered, to varying degrees, from Dutch Disease, with high export concentration in natural resource commodities and in a few foreign markets, and little development of their non-resource economies. The three countries' ability to create a sustainable path to economic growth and poverty reduction is inextricably linked to their connectivity with external markets, in the region and beyond. Thus, Mali, Niger, and Chad are first challenged by their geography -- their landlocked nature creates a barrier to market access beyond their immediate neighbors, while their vast and thinly populated lands serve to isolate the most vulnerable communities from external and internal markets. Adding to these geographic disadvantages, the incentive environment -- defined by high and variable customs common external tariff regimes resulting from multiple overlapping regional trade arrangements -- places a wedge between domestic and international prices that provides a disincentive to exports in favor of non-tradable and domestic-oriented sectors. By bringing greater coherence and convergence between the many common external tariff regimes in operation and the rationalization of their structures, and improving connectivity within and between markets, Mali, Niger, and Chad can better promote the reallocation of resources toward tradable goods and services, putting the countries on a path toward greater economic inclusion and sustainable growth.